An analysis of reference queries and answer-providing sources at the Filipiniana Section of the University of the Philippines Main Library, 1981-1983 - Mallari, Florenda D. (1984)
Reference work has been one of the major functions of the senior staff at the Filipiniana Section in the University of the Philippines Main Library. Through the years, this kind of service has been reflected in the annual reports only by the statistics of reference books and pamphlets used and in the number of reference questions handled by the reference staff. For a better understanding of this reference function, an analysis of reference questions was conducted to: 1) find out the types of questions asked by library inquirers at the Filipiniana Section; 2) identify the modes of transaction employed in referring the questions to the reference librarians; 3) determine the types of information or subjects inquirers generally looked for; 4) identify the answer-providing sources consulted by the librarians in answering the queries; 5) determine the cause/s of failure to answer some questions; and 6) identify the weaknesses of the reference service and make recommendations for improvement.